Transformasi Denpasar dari Kota Agraris Menjadi Kota Budaya, 1906-1979 - Girindrawardani, Anak Agung Ayu Dewi; Trisila, Slamat (Perkumpulan Program Studi Sejarah Se-Indonesia, 2024)
It does not seem to appear that Denpasar, the current capital of Bali Province, was originally an agricultural city and was not designed as a modern city. However, the modern city of Denpasar was formed due to power shifts, the development of cultural tourism, and the circulation of trade, both regional and international, in Bali since the beginning of the 20th century. This article aims to convey the written history of Denpasar City, 1906–1979, from socio-economic and cultural aspects. This essay uses historical methods as a tool to dissect and explain the changes that occurred in Denpasar City over 60 years. The transformation of Denpasar developed from initially being an agricultural city to becoming a cultural city at the beginning of the 20th century. The colonial era was the starting point for the modernization of Denpasar in terms of physical development, but on the other hand, the Dutch, with their Baliseering policy, made Bali, including Denpasar, a living museum. Denpasar, which was initially more agricultural, with the provision of various facilities both planned by the colonial government and those that developed spontaneously, is moving towards becoming an urban society. The establishment of Akademi Seni Tari Indonesia (ASTI, now Institut Seni Indonesia (ISI) Denpasar) in 1967, the construction of the Bali Art Center in 1978, and the launch of the Bali Arts Festival in Denpasar in 1979 as the launch of the Bali Arts Festival in Denpasar in 1979 as the peak of Balinese cultural activities made Denpasar a barometer of cultural cities and Bali Cultural Center.